An Interpretation of Religion - Hick, J. author. aut Link
XLII, 416 p.
Keywords: An updated new edition of the groundbreaking investigation which takes full account of the finding of the social and historical sciences whilst offering a religious interpretation of the religions as different culturally conditioned responses to a transcendent Divine Reality. Written with great clarity and force, and with a wealth of fresh insights, this major work (based on the author's Gifford Lectures of 1896-7) treats the principal topics in the philosophy of religion and establishes both a basis for religious affirmation today and a framework for the developing world-wide inter-faith dialogue. Includes a new Introduction to the second edition.